2011
DOI: 10.1007/s00268-011-1019-5
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Liver Transplantation Using Hepatitis C Virus‐Positive Donor Allografts: Case‐Controlled Analysis of the UNOS Database

Abstract: This is the first population-based analysis to show that after adjusting for donor and recipient characteristics there was no difference in graft or patient survival with the use of HCV+ donor liver allografts compared to HCV- donor liver allografts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…However, it has been clearly shown that the survival and progression of HCV disease is similar to HCV negative allografts [70]. Therefore, HCV+ grafts are increasingly used by transplant centres [71].…”
Section: A Anti-hcv Positive Donorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been clearly shown that the survival and progression of HCV disease is similar to HCV negative allografts [70]. Therefore, HCV+ grafts are increasingly used by transplant centres [71].…”
Section: A Anti-hcv Positive Donorsmentioning
confidence: 99%
“…The use of these liver grafts has been associated with higher rates of graft failure and biliary complication, particularly ischemic type cholangiopathy, compared with donation after brain death (DBD) allografts [84]. Optimum outcome has been shown if the WIT does not exceed 30 minutes, the CIT is limited to less than 8 hours, and younger donors being used (<50 years) [71]. There were no biliary or vascular complications and patient and graft survival is 100% at a median follow-up of 41.8 months (1.7-74 months) [89].…”
Section: ) Donors After Cardiac Deathmentioning
confidence: 99%
“…HBV: Hepatitis B virus. equivalent results in terms of frequency and severity of HCV recurrence, graft and patient survival [50,51] . Though the patient numbers in these studies are small and they are all retrospective studies, the evidence is promising.…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…They found that increasing number of mismatches was associated with increased risk of acute rejection though the graft survival rates were similar. In contrast, Muroetal [51] analysed data from 242 liver transplants and reported that matching at HLA-A locus increased the risk of graft failure. There is hence a lack of clarity regarding the relevance of HLA matching in LT.…”
Section: Hla Matchingmentioning
confidence: 99%
“…35 UNOS/OPTN registry analysis has shown comparable patient and graft survival for recipients of HCVAb+ versus HCVAb− grafts from 1994 to 2008. 99,100 Whether grafts from HCVAb+ donors are associated with more rapid HCV recurrence remains controversial. In 1 multicenter study of = US transplant centers, recipients of HCVAb+ (n = 99) compared with HCVAb− (n = 1107) liver recipients experienced a 58% increased risk of advanced fibrosis, defined as Ludwig-Batts stage 3 or 4 disease.…”
Section: The Spectrum Of Donor Quality: Ideal Standard and Expandedmentioning
confidence: 99%